Scalloped Implant-Abutment Connection Compared to Conventional Flat Implant-Abutment Connection: a Systematic Review and Meta-Analysis - Thomas Starch-Jensen; Ann-Eva Christensen; Henning Lorenzen (eJournal of Oral Maxillofacial Research)
Objectives: The objective was to test the hypothesis of no difference in implant treatment outcome after installation of implants with a scalloped implant-abutment connection compared to a flat implant-abutment connection.